Pengaruh Citra Merek, Promosi, Brand Trust Terhadap Brand Loyalty Pada Produk Skincare Skintific (Studi Penelitian : Masyarakat Kota Surakarta) - Putri, Nadya Kusuma; Kusdiyanto, Kusdiyanto (Paradoks : Jurnal Ilmu Ekonomi, 2025)
When consumers have a consistent tendency to choose products or services from a brand over a long period of time, it creates a solid foundation for business continuity. A strong commitment to a particular brand is reflected in a stable and consistent preference, which in turn increases trust and long-term relationships between brands and consumers. In an increasingly fierce competition, maintaining customer loyalty is not just about maintaining market share, but also about building a solid foundation for business growth and sustainability. Therefore, an effective strategy to increase brand loyalty is essential to differentiate yourself and gain a competitive advantage in the market.